A one-dimensional axisymmetric model for time-varying electromagnetic mitigation of plasma for alleviation of radio communication blackout - Donglin Liu; Xiaoping Li; Yanming Liu; Jiahao Xu; Fan Lei; Xi Chen (AIP Advances, 2018)
A high speed vehicle passing through the atmosphere may encounter radio communication blackout, a phenomenon which is caused by the high plasma density in the plasma layer surrounding the vehicle. To alleviate blackout, a method known as time-varying electromagnetic mitigation of the plasma (TEMP) is proposed. The principle of TEMP is based on a one-dimensional axisymmetric model consisting mainly of the ion mass conservation equation, the ion momentum conservation equation, the generalized Ohm's law and the electromagnetic induction law. Numerical simulations were performed to examine the plasma mitigation effects under various conditions by assuming a linearly decreasing magnetic field. Simulation results suggested that the plasma density at the center was reduced to less than 0.2 times the original plasma density but was of sufficient size (about 3 cm) and time duration (about 50 μs) to permit data transmission at pressures as high as 50 Pa. Furthermore, it is suggested that a lower pressure, stronger magnetic field and shorter duration are helpful for plasma mitigation, achieving nearly the same effect as that obtained at different plasma densities. Given that a dc magnet or a dc electric field is not required, and the power requirement and weight are modest, the TEMP approach based on applying a periodic magnetic pulse may be a promising way to alleviate radio communication blackout.